Otomatisasi Pengontrolan Kualitas Air Pada Akuarium Ikan Arwana Berbasis IOT Menggunakan Logika Fuzzy Tsukamoto - Ade Muhamad Nurhadi; Dwi Marisa Midyanti; Suhardi Suhardi (Universitas Budi Darma, 2023)
Arowana fish is an ornamental fish that has a beautiful body shape and color that makes it have a high price, and requires excellent care. The quality of the water in the aquarium must be maintained so that the Arowana fish are not stressed, sick, or die. However, many Arowana owners do not monitor water conditions closely. Therefore, a system is needed that can monitor the state of the aquarium environment, including automatic and manual water changes from the website. In this study using Arduino uno as a microcontroller connected to a pH and turbidity sensor, then NodeMCU ESP32 was used to send data to the internet and to perform the calculation process of Tsukamoto's fuzzy logic. The test results obtained an average accuracy on pH sensors of 96.62%, on turbidity sensors an average accuracy of 92.84%, on ultrasonic sensors an average accuracy of 99.62%. The system also tested Tsukamoto's fuzzy logic where the results were fuzzy with an accuracy of 83%. Testing of the system as a whole was carried out for 4 days. From the tests carried out, the average water pH per day results are 7.1 and turbidity of 18 NTU and all water quality conditions can be met according to the desired output using 9 rule bases.